Online group therapies for anxiety, obsessive-compulsive, and trauma-related disorders: a systematic review - Laurito, Luana D.; dos Santos-Ribeiro, Samara; Moreira-de-Oliveira, Maria E.; Loureiro, Carla P.; Hühne, Verônica; Torres, Bianca; de Faro, Livi Ferreira Testoni; de Menezes, Gabriela B.; Fontenelle, Leonardo F. (Frontiers in Human Neuroscience, 2024)
This systematic review examined the existing literature to determine the evidence supporting the efficacy of online group treatments for Anxiety-, Obsessive-Compulsive-and Trauma-Related Disorders (AOTDs). METHODS: A systematic review using the PUBMED, PsycInfo, Web of Science, and ClinicalTrials databases with no language, date, or study design filters was performed. The inclusion criteria comprised studies that examined individuals who had received a formal diagnosis of AOTDs, were aged 18 years or older, and had baseline and endpoint assessments of symptom severity using formal tools. RESULTS: Five studies on social anxiety disorder (SAD), four on post-traumatic stress disorder (PTSD) and one on tic disorders (TDs) were found. The studies were open-label (n= 2) and randomized controlled trials (RCTs) (n= 8), with five of the RCTs being non-inferiority trials. Most studies were conducted in the US and investigated psychological CBT based interventions via internet-based therapies (IBT: n= 4), video teleconferencing (VTC: n= 5) or a combination of both (n= 1). In SAD, IBT studies associated with a clinician assisted web-based forum (here termed "forum-enhanced" studies) were superior to waiting lists and not inferior to similar versions that were also "forum enhanced" but self-guided, "telephone enhanced" by a contact with a non-specialist, and "email enhanced" by a contact with a clinician individually. Studies involving VTC have shown comparable effectiveness to in-person interventions across some online group CBT based treatments for PTSD. Two open trials also demonstrated symptoms reductions of social anxiety and tics through VTC. CONCLUSIONS: There is evidence supporting the effectiveness of online group treatments for SAD and PTSD. Further studies from different research groups may be needed to replicate the use of 2 This is a provisional file, not the final typeset article these and other forms of online treatments in individuals with SAD, PTSD, and other clinical populations, such as OCD, panic disorder, agoraphobia and specific phobias.